ANALISIS EFEKTIVITAS IKLAN TELEVISI KOPI INSTAN TOP COFFEE ENDORSER â€IWAN FALSâ€ - Setyawan, Iwan (Department of Management, 2014)
This study aims to measure the effectiveness of television advertising endorser Top Coffee